The Effect of Scientific-Based E-Worksheet on Hydrocarbon Material on Students’ Critical Thinking Ability at Vocational High Schools - Nursera Nursera; Susilawati Susilawati; Rasmiwetti Rasmiwetti (STAI Hubbulwathan Duri, 2023)
The purpose of this reasearch was to know the effect of scientific-based e-worksheet on hydrocarbon material on student’s critical thinking ability at vocational high schools. The method used in this study was pre-experimental and the research design was one group pre-test and post-test with one experimental class and no control class. The population in this study were students of class X of a state vocational high school in Pekanbaru, while the number of samples were 30 students in class X RPL (Software Engineering), who were selected by purposive sampling technique. The instrument used to obtained data of students' critical thinking skills was multiple-choices (a, b, c, d and e) with total of 25 questions and each question has 4 points. Data of pre-test and post-test was analyzed with N-gain score. The results showed that pre-test was 44% and post-test was 88%. The average N-Gain score was found to be 0.7745 with high criteria. It could be stated that there was a significant difference between the pre-test and post-test scores on students' critical thinking skills. Furthermore, the average percentage of the N-Gain score was 77.4483% with effective criteria. It could be concluded that the scientific-based e-worksheet on hydrocarbon material was declared effective for training students' critical thinking skills at vocational high school.